Addressing Healthcare Access Inequalities in South Africa: Evaluating Legislative and Human Rights Obligations and Proposing Strategies for Improvement - Mlondolozi Mvikweni (E-Journal of Humanities, Arts and Social Sciences)
The study employed a mixed-methods approach, combining qualitative and quantitative research methodologies. A comprehensive review of legislative documents, including the National Health Act, the Promotion of Access to Information Act, and the Protection of Personal Information Act, was conducted to assess their impact on healthcare access. The findings revealed significant gaps in healthcare access, particularly among low-income and rural populations. Despite comprehensive legislation, implementation challenges and resource constraints hinder effective access to care. The study highlights discrepancies between policy intentions and real-world outcomes, with particular emphasis on systemic issues such as inadequate healthcare infrastructure and limited financial resources. The study recommends several strategies for improvement, including enhancing the implementation of existing healthcare laws, increasing investment in healthcare infrastructure, and developing targeted programs to address the specific needs of marginalized communities. Additionally, it suggests strengthening oversight mechanisms to ensure compliance with human rights obligations and improving data collection to understand better and address access disparities. Finally learning from Cuba’s healthcare model to improve the South African Healthcare System. This study adds to the existing body of knowledge by conducting a thorough assessment of healthcare accessibility in South African legislation and its alignment with human rights standards. It offers practical recommendations for policymakers and stakeholders, aiming to close the space between legal frameworks and healthcare delivery. By highlighting the challenges and proposing actionable strategies, the study provides valuable insights for improving healthcare access and addressing inequalities in South Africa.